Legal Reform and its Context in Vietnam - Quinn, Brian J. M. (Columbia Journal of Asian Law, 2002)
Vietnam has been undergoing economic reform since 1986. An important part of that reform has been a re-examination of the role of the courts and the bureaucracy in the resolution of disputes. Vietnam’s leadership has expressed the need to create rule by law in accordance with market principles as opposed to the rule of the bureaucracy that marked the centrally planned economies. The movement from the rule of the bureaucracy to rule by law is not necessarily a fast or an easy one. In the case of Vietnam, the ongoing tensions between the system that is hoped for and the system as it currently exists often create perverse or simply unexpected outcomes. On the one hand, domestic businessmen and parties to disputes seem to have been able to quickly understand the lay of the land in the gray area between rule by law and the rule of the bureaucracy. That understanding implies an ability to navigate the ‘system’ and an ability to navigate it with a certain degree of accuracy and reasonable expectation of achieving an outcome. This paper attempts to describe the gray area and how parties are able to navigate the system in Vietnam.